Methylated Barbituric Acid-Functionalized Tetraphenylethylene: Aggregation- Induced Emission, Mechanochromism, and Optical Wave-Guiding Properties - Ge, Sheng; Xu, Xiangjun; Xu, Ziqiang; Wang, Erjing; Li, Dongqin; Wang, Shimin (Current Chinese Science, 2022)
Background: Restrained by the aggregation-causing quenching of conventional fluorophores, the design and synthesis of solid-state emissive materials is a persistent pursuit for scientists. The discovery of aggregation-induced emission provides an efficient strategy for preparing solidstate emissive luminogens. Objective: A multifunctional solid-state emissive material DMBTPE was prepared from tetraphenylethylene and N-methylated barbituric acid through the construction of donor-acceptor structure. Methods: DMBTPE showed typical aggregation-induced emission characteristics: non-emissive when molecularly dissolved in solution while strongly emissive in the aggregated state or as solid. Owing to the strong donor-acceptor interaction, the maximum absorption of DMBTPE shifted to the visible light region. DMBTPE also exhibited reversible mechanochromic fluorescence with 30-40 nm emission wavelength change. Results: DSC and XRD results indicated the transition between the amorphous state and crystalline state was accounted for the mechanochromic fluorescence behavior. The microcrystalline rods of DMBTPE grown from hot ethanol solution exhibited good optical waveguiding effect and the optical loss was as low as 0.018 dB/μm. Conclusion: DMBTPE was an efficient solid emitter. Such attributes enable this kind of materials to find wide applications in many areas, such as biological imaging and optoelectronic devices.
Keywords: mechanochromism